Pengaruh Media Pembelajaran Wordwall Quiz terhadap Hasil Belajar Siswa Kelas VIII pada Pembelajaran PPKn di SMP Swasta Pahlawan Nasional - Theresia Saragih; Maryatun Kabatiah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Pancasila and Citizenship Education (PPKn) learning at the junior high school level is often considered monotonous by students because the method of delivering material tends to be repetitive and less varied. This has an impact on low motivation and student learning outcomes. This study aims to determine the influence of the use of Wordwall media on the learning outcomes of grade VIII students in PPKn subjects. Wordwall is an interactive digital-based learning media designed to create a fun learning experience through various educational games, such as quizzes, matching, and gameshows. The research method used was a quasi-experiment with a nonequivalent control group design, which involved two groups: the experimental group (VIII-3) using Wordwall media, while the control group (VIII-6) followed conventional learning. The sampling technique was carried out by purposive sampling. The research data was collected through objective test questions that measured students' understanding of the periodic element material in PPKn. The results showed a significant difference between the experimental and control groups. The average post-test score of the control group was 68.79, while the experimental group reached 85.86. The Paired Samples Test yielded a significance value of 0.000 < 0.05, so the null (Ho) hypothesis was rejected and the alternative hypothesis (Ha) was accepted. This proves that the use of Wordwall media has a positive and significant impact on improving student learning outcomes. Based on these findings, it is recommended that PPKn teachers integrate Wordwall regularly in learning, for example at the stage of evaluation or reinforcement of material. Wordwall can be combined with discussion or collaborative learning methods to increase student active participation. Teachers are also advised to develop an interactive question bank on Wordwall that is relevant to the curriculum so that students can practice independently. With this approach, it is hoped that PPKn learning will be more interesting, effective, and able to build students' emotional involvement in understanding Pancasila values.